CD8+ T cells in brain injury and neurodegeneration - Zhang, Zhaolong; Duan, Zhongying; Cui, Yu (Frontiers in Cellular Neuroscience, 2023)
The interaction between the peripheral immune system and the brain is increasingly being recognized as an important layer of neuroimmune regulation and plays vital roles in brain homeostasis as well as neurological disorders. As an important population of T-cell lymphocytes, the roles of CD8+ T cells in infectious diseases and tumor immunity have been well established. Recently, increasing number of complex functions of CD8+ T cells in brain disorders have been revealed. However, an advanced summary and discussion of the functions and mechanisms of CD8+ T cells in brain injury and neurodegeneration are still lacking. Here, we described the differentiation and function of CD8+ T cells, reviewed the involvement of CD8+ T cells in the regulation of brain injury including stroke and traumatic brain injury and neurodegenerative diseases, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), and discussed therapeutic prospects and future study goals. Understanding these processes will promote the investigation of T-cell immunity in brain disorders and provide new intervention strategies for the treatment of brain injury and neurodegeneration.